Rapid assessment of avoidable blindness and diabetic retinopathy in Republic of Moldova. Issue 6 (30th December 2014) - Zatic, Tatiana; Bendelic, Eugen; Paduca, Ala; Rabiu, Mansour; Corduneanu, Angela; Garaba, Angela; Novac, Victoria; Curca, Cristina; Sorbala, Inga; Chiaburu, Andrei; Verega, Florentina; Andronic, Victoria; et al.
Abstract : Objective: To evaluate the prevalence and causes of blindness and visual impairment, the prevalence of diabetes mellitus and diabetic retinopathy among people aged ≥50 years in the Republic of Moldova using Rapid Assessment of Avoidable Blindness plus Diabetic Retinopathy ('RAAB+DR') techniques. Materials and Methods: 111 communities of people aged ≥50 years were randomly selected. In addition to standard RAAB procedures in all people with diabetes (previous history of the disease or with a random blood glucose level >11.1 mm/L (200 mg/dL)), a dilated fundus examination was performed to assess the presence and the degree of diabetic retinopathy using the Scottish DR grading system. Results: 3877 (98%) people out of the 3885 eligible people were examined. The prevalence of blindness was 1.4% (95% CI 1.0% to 1.8%). The major causes of blindness and severe visual impairment were untreated cataract (58.2%), glaucoma (10.9%), and other posterior segment causes (10.9%). The estimated prevalence of diabetes was 11.4%. Among all people with diabetes, 55.9% had some form of retinopathy, and sight threatening diabetic retinopathy affected 14.6%. Conclusions: The RAAB+DR survey in the Republic of Moldova established that untreated cataract is the major cause of avoidable blindness in rural areas. This needs to be tackled by expanding the geographical coverage of cataract surgical services.